Correlation between prevalence and socio-demographic, knowledge and risk factors of soil transmitted helminthiases: cross-sectional study among primary school-going children in Rarieda, Kenya - Arwa, Stephen Onyango; Mogere, Dominic; Musoke, David (International Journal Of Community Medicine And Public Health, 2020)
Background: Soil transmitted helminthiasis, classified as neglected tropical diseases are among the most common infections worldwide with greatest numbers occurring in Sub-Saharan Africa, Americas, China and East Asia. Globally, over two billion people are infected with school-age children bearing the greatest burdens. Transmission is through eggs present in human faeces. They are infections of public health importance as they cause among others, nutritional impairment, diarrhoea and intestinal obstruction. Prevention involves deworming, health education and sanitation. Methods: The study was carried out in Rarieda, Kenya in 2018. Study participants were primary school children of ages seven to fifteen. Cross sectional study design was used and the data was analyzed using Statistical Package for Social Sciences. All the ethical issues were adhered to as per the International standards. Results: The study established that prevalence of soil transmitted helminthiasis was high in areas where the risk factors associated with the infections were high. Pupils who were more knowledgeable on soil transmitted helminthiases were less infected. Younger pupils were more infected than older pupils. Lastly, the prevalence of these infections varied with gender of the pupils, and geographical location from where the pupils came from. Conclusions: Correlation between prevalence of soil transmitted helminthiases and risk factors, and between presence of toilets and level of hygiene practice were positive, r=0.90 and 0.93 respectively; while correlation between prevalence of soil transmitted helminthiases and knowledge was negative, r=-0.75. Values of the correlations were of statistical significance at p<0.05.